Applications, challenges, and opportunities of blockchain technology in banking and insurance - Gupta, S. L.; Kansra, Pooja, 1984-; Kukreja, Gagan, 1974- (Information Science Reference, 2022)
"This book offers an overall image of the evolution of blockchain technology and its application concerning warehouse or storage management in the development of operation networks and presents critical problems and proposed initial solutions for the blockchain technology's application in the banking and Insurance sectors"--